Creating a place for us: an overview of the FICE young people's conference 2004 - Irene Stevens (Scottish Journal of Residential Child Care)
Conferences like this allow us to get together, to share information, experiences and more importantly, it gives us an excellent opportunity to make friends. Throughout the last three days I’ve laughed, danced, played sport and, most importantly, learnt so much about different cultures and nationalities. Not all of us speak the same language and yet we have managed to communicate and laugh together.